ANALISIS PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA PEGAWAI - Alwi Suddin, Arum Sari (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
Purpose of this research to analyze the effect of compensation, work environment and career development on employee satisfaction. Population of this research on PT Pegadaian Area Surakarta. The sampling technique used sensus with 52 samples. The type of data used quantitative and qualitative data. Source of data used primary data and secondary data. The technique of collecting data used questionnaires and literature. The data analysis technique used multiple linear regressions. The results showed that compensation has significant effect on employee work satisfaction. Work environment has significant effect on employee work satisfaction. Career development has significant effect on employee work satisfaction. Compensation is the dominant variable effect on employee work satisfaction. Keywords: compensation, work satisfaction, career development, work satisfaction.